Electrochemical investigation of the effect of temperature, salinity and salt type on brine/mineral interfacial properties - Arif, Muhammad; Jones, Franca; Barifcani, Ahmed; Iglauer, Stefan (Elsevier, 2017)
CO2 wettability of minerals and CO2/brine interfacial tension are critical parameters that significantly influence the underground geological storage of CO2. These interfacial phenomena are proven to be a function of pressure, temperature, salinity and salt type. However, there is a clear lack in understanding of the principal mechanisms such as the electrochemical interactions at the brine/mineral interface, which are responsible for altering wettability. Moreover, the literature lacks experimental data on contact angle and interfacial tension for a broad range of salinity conditions. Therefore, in this article, we investigated the electrochemical processes at the brine/mica interface by measuring the zeta potentials of brine/mica systems as a function of temperature (298 K–343 K), salinity (0 wt% NaCl–5 wt% NaCl) and salt type (NaCl, CaCl2, MgCl2) and we measured advancing and receding contact angles for the same experimental matrix to derive the relationship between surface charge (at the brine/mineral interface) and wettability. Further, we measured advancing and receding contact angles for 20 wt% CaCl2 and 20 wt%MgCl2 at high pressures (0.1 MPa–20 MPa) and a temperature of 323 K, and CO2-brine interfacial tensions for the same conditions to allow wettability characterization at a broader scale. Such investigations are aimed at understanding and reducing the risk associated with CO2 geo-storage projects, by allowing the conceptual understanding of the factors influencing wettability. Finally, we provided a guided estimate of CO2 column heights that can be permanently immobilized beneath the caprock, and we found that elevated temperature and less saline brine lead to better storage capacities.